Pengaruh Digital Konten Marketing Media Sosial Tiktok Terhadap Brand Image Produk Scarlett Whitening (Studi Kasus Pada Mahasiswa UNTIDAR): Studi Kasus Pada Mahasiswa UNTIDAR - Muthohar, Abda Fahmi; Hartono, Budi (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The Tiktok social media in Indonesia is widely used for creativity and for doing business with the public. One company that implements this strategy is Scarlett Whitening. Scarlett Whitening is a beauty product from Indonesia that is intensively marketed through social media, especially on social media such as TikTok, by creating digital content and collaborating with influencers to build a brand image on its products. This research was conducted to determine how much digital influence Tiktok's social media marketing content has on the brand image of Scarlett Whitening products. This study's independent variable is TikTok's digital marketing content, while the dependent variable is the brand image. This quantitative research uses multiple linear regression analysis, normality tests, correlation analyses, coefficient of determination, and hypothesis testing (T-test and F-test). The results of the study indicate that there is an influence of Tiktok's digital marketing contacts on the brand image of Scarlett Whitening products. The results of the analysis of the coefficient of determination obtained were 0.411. So it can be explained that the independent variable, namely digital content marketing Tiktok, influences 41.1% while the remaining 58.9% is influenced by other variables not in this study.